Dr. Ara A. Chrissian: the key components to a successful Pulmonary and Critical Care Medicine training program - Pei, Tina Chu (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Dr. Ara A. Chrissian (Figure 1) is visiting us from the United States as part of a training collaboration between Henry Ford Hospital in Detroit, USA and two hospitals in China: Changhai Hospital at the Second Military Medical University in Shanghai, and the Guangzhou Medical University here in Guangzhou.